Throwing the Ball Game Improves Students’ Speaking Skills - Rahmadhani, Nabila Putri; Asfar, Shafira; Authar, Nailul (Jurnal Pendidikan Anak, 2021)
The aims of the study is is to improve the students’ speaking skills through communicative. And the subject for this research is coming from Courses Student.  The communicative games implemented was a Throw the Ball game.  The type of the data is qualitative data which the researcher get through interviews and test. The findings showed good improvement to students’ speaking skills. Most students enjoy the game while laughing, some students are a little confused when suddenly asked questions and cause their answers to go round and round, students are forced to get out of the situation and they succeed. Moreover, students hold highly positive attitudes about the role of games in improving their speaking skills.